The impact of Formal and Informal Employment of women on their Quality of Life: a study in Tehran - Abolghasem Pourreza; Marzye Rostaminya; Touraj Harati Khalilabad; Sara Maleki; Seyed Abdolreza Mosavi (Kerman University of Medical Sciences, 2018)
Background & Objectives: Women have a basic role in ensuring the health of future generations and their employment forms an important part of their life. Changes in the traditional roles of women and their growing demand for participation in various job positions, have become an undeniable fact of Iranian society. The purpose of this study was to investigate the effect of formal and informal employment on women's quality of life. Methods: This was a cross-sectional descriptive-analytic study performed from December 2016 to July 2017 on 112 formal employed women and the same number of informal employed women who were randomly selected. To assess subjects' quality of life, SF-36 standard questionnaire was used as a valid tool. Data were analyzed using Mann-Whitney and independent t- test statistical tests and through SPSS version 21 software. Results: According to the results, 49.1% of women working in the informal sector did not have high school diploma and were younger than 24 years old. The mean score of quality of life in women employed in the formal sector (78.95 ± 13.6) was significantly better than that of women employed in the informal sector (84.77 ± 10.21) (P<0.05). Conclusion: Due to the rapid growth of the informal sector following social and economic issues, the number of women working in the informal sector is increasing. Lack of insurance and adequate salary are some of the problems in the informal sector. Government intervention in the informal sector through implementing related laws is a strategy to solve the problems of women working in the informal sector of the country. Keywords: Women employing, Quality of life, Formal employment, Informal employment Citation: Pourreza A, Rostaminya M, Harati Khalilabad T, Maleki S, Mosavi SA. The impact of Formal and Informal Employment of women on their Quality of Life: a study in Tehran. Journal of Health Based Research 2018; 3(4): 379-388.